Pengaruh Akupresur Terhadap Emesis Gravidarum Pada Ibu Hamil Trimester I di Praktik Bidan Hj. Hemawati Kecamatan Bambel Kabupaten Aceh Tenggara Tahun 2023 - Fithriani, Fithriani; Nasution, Herlia Sumardha; Husni, Fadhilah Ikhwa (Jurnal Media Informatika, 2024)
Emesis gravidarum occurs in pregnant women during the first trimester of pregnancy. This condition is called emesis gravidarum, or layman calls emesis gravidarum in the morning called morning sickness, but this condition experienced by mothers not only occurs in the morning, but can also occur in the afternoon, evening and night. The purpose of the study was to determine the effect of acupressure on emesis gravidarum in first trimester pregnant women at Hj. Hemawati Clinic, Southeast Aceh Regency in 2023. This research design is a pre-experimental method with one-group pretest- posttest design. The population in this study was all the first timester pregnant women who experienced emesis gravidarum, with accidental sampling techniques and obtained samples of 20 respondents. The research time starts from March- August 2023, which is carried out August 14-27, 2023. Data analysis using the Wilcoxon test. The results showed that before acupressure was carried out on emesis gravidarum in first trimester pregnant women, the frequency distribution was known to be moderate, while after acupressure was carried out on emesis gravidarum in first trimester pregnant women, the frequency distribution was known to be light, it can be concluded that there is an effect of acupressure on emesis gravidarum in first trimester pregnant women before and after acupressure because it obtained value = 0.000 < 0.05. Conclusion There is an influence before and after acupressure on emesis gravidarum in pregnant women in the first trimester of pregnancy. Southeast Aceh should inform the importance of acupressure to reduce emesis gravidarum.